Flour food waste derived activated carbon for high-performance supercapacitors. Issue 92 (19th September 2016) - Zhan, Changzhen; Yu, Xiaoliang; Liang, Qinghua; Liu, Wei; Wang, Yanbo; Lv, Ruitao; Huang, Zheng-Hong; Kang, Feiyu
Abstract : Activated carbon was prepared by carbonization of flour food waste residue and subsequent KOH activation. It shows great prospects in high-performance supercapacitor applications. Abstract : It is of great importance to develop electrode materials at a low cost for constructing high-performance electrochemical energy storage systems. Herein, we employed flour food waste residue as a raw material to prepare porous carbon based supercapacitor electrodes through the carbonization and subsequent KOH activation process. The as-prepared biomass-derived activated carbon exhibits an interconnected porous network with numberous open micropores and appropriate mesopores. Meanwhile, its moderate total pore volume results in a high mass density of 0.86 g cm −3 . When used as supercapacitor electrodes in an aqueous solution of KOH (6 mol L −1 ), the porous carbon material shows a high specific capacitance (278 F g −1, 241 F cm −3 ) and good cycling stability with 95% capacitance retention over 3000 cycles at a current density of 2 A g −1 . Furthermore, even at an ultrahigh current density of 100 A g −1 (charge/discharge completed within 3 s), it still maintains a high specific capacitance of 142 F g −1 (122 F cm −3 ).